Risk factors for mortality in Asian Taiwanese patients with methanol poisoning - Lee CY; Chang EK; Lin JL; Weng CH; Lee SY; Juan KC; Yang HY; Lin C; Lee SH; Wang IK; Yen TH (Dove Medical Press, 2014)
Chen-Yen Lee,1,* Eileen Kevyn Chang,1,* Ja-Liang Lin,1 Cheng-Hao Weng,1 Shen-Yang Lee,1 Kuo-Chang Juan,1 Huang-Yu Yang,1 Chemin Lin,2 Shwu-Hua Lee,2 I-Kwan Wang,3 Tzung-Hai Yen1 1Department of Nephrology and Division of Clinical Toxicology, 2Department of Psychiatry, Chang Gung Memorial Hospital and Chang Gung University, Taipei, Taiwan; 3Department of Nephrology, China Medical University Hospital and China Medical University, Taichung, Taiwan *These authors contributed equally to this work Introduction: Methanol poisoning continues to be a serious public health issue in Taiwan, but very little work has been done to study the outcomes of methanol toxicity in the Asian population. In this study, we examined the value of multiple clinical variables in predicting mortality after methanol exposure. Methods: We performed a retrospective observational study on patients with acute poisoning who were admitted to the Chang Gung Memorial Hospital over a period of 9 years (2000–2008). Out of the 6,347 patients, only 32 suffered methanol intoxication. The demographic, clinical, laboratory, and mortality data were obtained for analysis. Results: Most patients were middle aged (46.1±13.8 years), male (87.5%), and habitual alcohol consumers (75.0%). All the poisonings were from an oral exposure (96.9%), except for one case of intentionally injected methanol (3.1%). After a latent period of 9.3±10.1 hours, many patients began to experience hypothermia (50.0%), hypotension (15.6%), renal failure (59.4%), respiratory failure (50.0%), and consciousness disturbance (Glasgow coma scale [GCS] score 10.5±5.4). Notably, the majority of patients were treated with ethanol antidote (59.4%) and hemodialysis (58.1%). The remaining 41.6% of patients did not meet the indications for ethanol therapy. At the end of analysis, there were six (18.8%), 15 (46.9%), and eleven (34.4%) patients alive, alive with chronic complications, and dead, respectively. In a multivariate Cox regression model, it was revealed that the GCS score (odds ratio [OR] 0.816, 95% confidence interval [CI] 0.682–0.976) (P=0.026), hypothermia (OR 168.686, 95% CI 2.685–10,595.977) (P=0.015), and serum creatinine level (OR 4.799, 95% CI 1.321–17.440) (P=0.017) were significant risk factors associated with mortality. Conclusion: The outcomes (mortality rate 34.4%) of the Taiwanese patients subjected to intensive detoxification protocols were comparable with published data from other international poison centers. Furthermore, the analytical results indicate that GCS score, hypothermia, and serum creatinine level help predict mortality after methanol poisoning. Keywords: wood alcohol, intoxication, ethanol, hemodialysis, mortality